Evaluation of Swelling – Shrinkage of Soil Stabilized with Cement and Spent Bleaching Earth - Nasiruddin (Jurnal Inovasi Teknologi, 2024)
This research aims to investigate the effect of using Spent Bleaching Earth (SBE) as a soil stabilizer in cement-stabilized soil. The study employs a 5% Portland Composite Cement (PCC) ratio based on the dry soil weight, with SBE as a stabilizing agent at ratios of 5%, 10%, 15%, and 20% of the Portland Composite Cement weight. Curing periods of 0 days, 7 days, and 14 days are used, with a focus on the expansion and shrinkage characteristics. The best results were obtained in a mixture with a 10% SBE variation as a soil stabilizer, under a 14-day curing period, with a plasticity index of 14.149%, Expansion (CBR Soaked) of 1.178, Expansion Pressure of 1,706 kg/cm2, and free expansion index of 13.333%. Test results indicate that mixtures with various amounts of SBE as a soil stabilizer in cement-treated soil and different curing periods can reduce soil expansion, as evidenced by decreasing values of plasticity index, Expansion (CBR Soaked), expansion pressure, and free expansion index. Therefore, it can be concluded that SBE as a soil stabilizer, along with prolonged curing, can reduce the soil's expansion and shrinkage characteristics.